Head first HTML with CSS and XHTML : a brain-friendly guide. - Freeman, Elizabeth, 1966-2024; Freeman, Eric, 1965- (Beijing : O'Reilly, 2006)
You want to learn HTML so you can finally create those web pages you've always wanted, so you can communicate more effectively with friends, family, fans, and fanatic customers. You also want to do it right so you can actually maintain and expand your Web pages over time, and so your web pages work in all the browsers and mobile devices out there. Oh, and if you've never heard of CSS, that's okay-we won't tell anyone you're still partying like it's 1999-but if you're going to create Web pages in the 21st century then you'll want to know and understand CSS. Learn the real secrets of creating Web pages, and why everything your boss told you about HTML tables is probably wrong (and what to do instead). Most importantly, hold your own with your co-worker (and impress cocktail party guests) when he casually mentions how his HTML is now strict, and his CSS is in an external style sheet. So what are you waiting for? Leave those other dusty books behind and come join us in Webville. Your tour is about to begin.
Inhoudsopgave : 1. The language of the Web 2. Meeting the 'HT' in HTML 3. Web page Construction 4. A trip to Webville 5. Meeting the media 6. Serious HTML 7. Putting the 'X' into HTML 8. Adding a little style 9. Expanding your vocabulary 10. Getting intimate with elements 11. Advanced web construction 12. Arranging elements 13. Getting tabular 14. Getting interactive 15. The top ten topics(we didn't cover)
Keywords: HTML; Programmeertalen; Webdesign; Websites ontwerpen; Websites